Probabilistic Earthquake Hazard Assessment in Indonesia Using Poisson Model and Spatial Grid Analysis - Hartati; Effendie, Adhitya Ronnie; Susyanto, Nanang; Suryanto, Wiwit (Science and Technology Indonesia, 2026)
Indonesia, located at the convergence of three major tectonic plates in the Pacific Ring of Fire (ROF), is highly susceptible to earthquakes. This study analyzes earthquake hazard in Indonesia using a statistical approach based on the Poisson distribution combined with spatial mapping through a 0.5o x 0.5o grid. Earthquake  data from the USGS catalog (1925–2025), including time, location, depth, and magnitude, were analyzed. Annual earthquake frequencies were calculated for each grid cell with magnitude ≥ 5.0, and the probability of at least one event occurring within 10, 25, and 50 years was estimated using the Poisson probability function. Results were visualized as spatial probability risk maps for 10-, 25-, and 50-year horizons, enabling the identification of earthquake-prone areas and classification of risk levels. The findings reveal that subduction zones, particularly along the Sunda Arc, exhibit probabilities exceeding 90% for M≥ 5 events within the next 50 years, highlighting their significance for disaster preparedness. These results demonstrate that a Poisson-based statistical and spatial approach is effective for probabilistic earthquake hazard mapping and provides direct support for disaster risk reduction and spatial planning in Indonesia.